1981
DOI: 10.1093/ptj/61.6.873
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Exercise Program on the Static Balance of Deaf Children

Abstract: Deaf children show subnormal performance on standard tests of static balance. This study investigated the effect of a 10-day exercise program of static balance activities on the static balance ability of severely deaf children. A pretest-posttest control group design was used. The subjects, 49 deaf children, were tested on a force platform in four different stances. The experimental group then participated in a daily exercise program of activities traditionally used to facilitate balance ability. A comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
2
12

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 5 publications
4
39
2
12
Order By: Relevance
“…Hearing-impaired individuals, in comparison to normal-hearing ones, are more vulnerable with regards to static balance, dynamic coordination of the body, simultaneous movements of limbs and movement speed (Eff gen, 1981;Fotiadou et al, 2002;Kitiş, Büker, Eren, & Aydın, 2015;Wiegersma & Velde, 1983;Yağcı, Cavlak, & Şahin, 2004). Th is impaired balance may aff ect the acquisition of other motor skills and may hinder visual-perceptual motor development and sensory integration (Eff gen, 1981). However, sport is a recommended method for reducing these negative eff ects, facilitating daily life activities and the rehabilitation of hearing-impaired individuals (Yağcı et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Hearing-impaired individuals, in comparison to normal-hearing ones, are more vulnerable with regards to static balance, dynamic coordination of the body, simultaneous movements of limbs and movement speed (Eff gen, 1981;Fotiadou et al, 2002;Kitiş, Büker, Eren, & Aydın, 2015;Wiegersma & Velde, 1983;Yağcı, Cavlak, & Şahin, 2004). Th is impaired balance may aff ect the acquisition of other motor skills and may hinder visual-perceptual motor development and sensory integration (Eff gen, 1981). However, sport is a recommended method for reducing these negative eff ects, facilitating daily life activities and the rehabilitation of hearing-impaired individuals (Yağcı et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Effgen [13] studied the effects of single leg stance practice on postural sway measures in 7-11-year-old children with hearing impairment and found no improvement. Lewis et al [14] reported that participation in a balance and body awareness program did result in improved balance skills in 6-8-year-old children with hearing impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Os resultados obtidos no presente estudo, embora sejam de uma amostra pequena, revelaram diferenças significantes entre os grupos dos surdos e dos ouvintes, no que se refere ao equilíbrio está-tico, sendo que o grupo dos ouvintes apresentou um desempenho melhor que o grupo dos surdos, como ocorreu nos trabalhos feitos por vários autores 8,18,19,23 nos quais as crianças portadoras de perda auditiva neurossensorial apresentaram um déficit na capacidade de equilíbrio estático, em comparação com as crianças ouvintes. Em relação ao desempenho  inferior dos surdos no teste de Romberg, cabe ressaltar que a retirada da pista visual (olhos fechados) compromete ainda mais a manutenção do equilíbrio destes indivíduos 5,7,9 , uma vez que, provavelmente, já possuem uma defasagem vestibular.…”
Section: Discussionunclassified
“…Após 10 dias de treinamento de atividades para melhorar o equilíbrio estático, não houve uma melhora significativa da performance dos sujeitos comparados com um grupo controle, porém o tempo em que eles conseguiram permanecer num pé só aumentou significantemente. O autor do trabalho sugeriu que investigações adicionais devem ser feitas de forma a esclarecer o papel de programas de exercícios para a melhora do equilíbrio estático 19 . Foi realizado um estudo com 40 crianças (idade média de 10 anos, aproximadamente) e foram observadas diferenças significativas no equilíbrio dinâmico de crianças com surdez neurossensorial comparadas com crianças ouvintes, sendo que estas últimas apresentaram um equilíbrio melhor.…”
Section: Introductionunclassified
See 1 more Smart Citation